1997
DOI: 10.1002/aic.690430509
|View full text |Cite
|
Sign up to set email alerts
|

Unique properties of 30‐μm particles as the catalyst of fluidized‐bed reactors

Abstract: The collapse properties of three kinds of fine particles (19, 30, and 59 p m )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…The collapsing curve has a sharp falling curve followed by a slower decline. The observed behavior was similar to that of the settling 3.18 curve of Yang, et al (1997) The critical velocity is 0.7 m/sec at a solid volume fraction of 0.02. It is similar to the Ding's experimental values (Gidaspow, et al 1986) in which the typical critical velocity value of the particulate phase was one meter per second.…”
Section: Pressure Drop and Minimumsupporting
confidence: 64%
“…The collapsing curve has a sharp falling curve followed by a slower decline. The observed behavior was similar to that of the settling 3.18 curve of Yang, et al (1997) The critical velocity is 0.7 m/sec at a solid volume fraction of 0.02. It is similar to the Ding's experimental values (Gidaspow, et al 1986) in which the typical critical velocity value of the particulate phase was one meter per second.…”
Section: Pressure Drop and Minimumsupporting
confidence: 64%
“…al. 1988 andYang et al 1997 observed that this happens so quickly that little useful data can be obtained. There is very little published data quantifying the rate of collapse of Geldart Group B particles.…”
Section: Geldart Groups and The Collapsing Fluidized-bed Experimentsmentioning
confidence: 99%
“…The collapse time for the bed containing Geldart Group C particles, as shown in Figure 12, is significantly longer than that of Geldart Groups A or B. Ž . As disucssed by Yang et al 1997 the faster collapse of fluidized beds containing Geldart Group C particles is due to the strong tendency for aggregation. This particle᎐particle attraction causes cracks or channels to form, allowing the gas to escape quickly.…”
Section: Simulation Of the Collapsing Fluidized Bedmentioning
confidence: 99%
See 2 more Smart Citations